Evangelical Christianity and democracy in Asia - Lumsdaine, David Halloran (Evangelical Christianity and democracy in the Global South, 2009)
Although a minority of the Asian population, Protestants in Asia are a fast growing group. In some cases, religion has effected positive changes for poor and marginalised people; but there are doubts that it has the cultural currency needed to generate political changes in governments such as that in China.